Management of Maillard reaction-derived reactive carbonyl species and advanced glycation end products by tea and tea polyphenols - Yue Luo; Jianan Zhang; Chi-Tang Ho; Shiming Li (Food Science and Human Wellness)
Tea as the most consumed beverage in the world has received enormous attention for its promoting health benefits. The deleterious effect of α-dicarbonyls and AGEs formed in Maillard reaction is also a long-term challenge. The connection between the two topics was the main aim of this review, to address and update the antiglycation effect and mechanism of tea and tea polyphenols. By analyzing recent publications, we have covered across chemistry models, cell lines and animal studies. Tea polyphenols, particularly catechins, showed outstanding antiglycation effect by trapping α-dicarbonyl compounds and impeding AGEs formation. Reduction of carbonyl stress brought alleviation to aging, diabetes, and collagen related diseases or complications through regulation of RAGE expression and subsequent MAPK and TGF-β pathway. Therefore, tea polyphenols can serve as promising natural candidates in the treatment and/or prevention of nephropathy, retinopathy, hepatopathy, hyperglycemia and obesity among others, by their potent antiglycation effect. Further studies need to address on aspects like exact mechanisms, solution of detection obstacles, balance of practical usage and harmful effects such as potential flavor damage and toxicity in food, to gain a comprehensive understanding of antiglycation activities of tea polyphenols and its actual application.